(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article delves into the intricate aspects of puncture of the upper jaw cavity, with a focus on the maxillary sinus. The study aims to provide a comprehensive understanding of the procedure, its potential complications, and the methods employed for successful intervention. Through a literature analysis, various approaches and outcomes are examined, leading to a detailed discussion of the results. The article concludes with insights into the implications of upper jaw cavity puncture, along with suggestions for future research and clinical practice.